Bilateral Proprioceptive Evaluation in Individuals With Unilateral Chronic Ankle Instability - Sousa, Andreia S. P. (2019)
Context: Despite extensive research on chronic ankle instability, the findings regarding proprioception have been conflicting and focused only on the injured limb. Also, the different components of proprioception have been evaluated in isolation. Objective: To evaluate bilateral ankle proprioception in individuals with unilateral ankle instability. Design: Cohort study. Setting: Research laboratory center in a university. Patients or Other Participants: Twenty-four individuals with a history of unilateral ankle sprain and chronic ankle instability (mechanical ankle instability group, n = 10; functional ankle instability [FAI] group, n = 14) and 20 controls. Main Outcome Measure(s): Ankle active and passive joint position sense, kinesthesia, and force sense. Results: We observed a significant interaction between the effects of limb and group for kinesthesia (F = 3.27, P = .049). Increased error values were observed in the injured limb of the FAI group compared with the control group (P = .031, Cohen d = 0.47). Differences were also evident for force sense (F = 9.31, P < .001): the FAI group demonstrated increased error versus the control group (injured limb: P < .001, Cohen d = 1.28; uninjured limb: P = .009, Cohen d = 0.89) and the mechanical ankle instability group (uninjured limb: P = .023, Cohen d = 0.76). Conclusions: Individuals with unilateral FAI had increased error ipsilaterally (injured limb) for inversion movement detection (kinesthesia) and evertor force sense and increased error contralaterally (uninjured limb) for evertor force sense